Edukasi Hipertensi dan Pemeriksaan Tekanan Darah serta Kolesterol pada Masyarakat Kelurahan Jati Karya, Binjai Sebagai Upaya Preventif Penyakit Komorbid Covid-19 - Wiryanto Wiryanto; Embun Suci Nasution; Aminah Dalimunthe; Ade Sri Rohani (Unri Conference Series: Community Engagement, 2021)
Lack of understanding of hypertension and its prevention in the community and still lack of health checks such as blood pressure and cholesterol checks so that the need and importance of community service in order to prevent comorbid diseases Covid-19. One way to prevent Covid-19 comorbid disease is to educate about hypertension, symptoms / signs and prevention against hypertension so that the public knows more about hypertension and can prevent suffering from hypertension, as well as free health checks that include blood pressure and cholesterol checks in the community in Jati Karya village, North Binjai sub-district and this is the purpose of this community service activity. Active Participant Community Based conducted in the form of training with the Active Participants Learning method and conducted health examinations including blood pressure and cholesterol checks, as well as monitoring and evaluation activities of community service. The results of the pre-test and post-test analysis based on the T-test showed a significant increase in patient knowledge (p<0.05).